2016
DOI: 10.1088/0264-9381/33/15/154002
|View full text |Cite
|
Sign up to set email alerts
|

Black holes and stars in Horndeski theory

Abstract: We review black hole and star solutions for Horndeski theory. For non-shift symmetric theories, black holes involve a Kaluza-Klein reduction of higher dimensional Lovelock solutions. On the other hand, for shift symmetric theories of Horndeski and beyond Horndeski, black holes involve two classes of solutions: those that include, at the level of the action, a linear coupling to the Gauss-Bonnet term and those that involve time dependence in the galileon field. We analyze the latter class in detail for a specif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
149
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 112 publications
0
149
0
Order By: Relevance
“…[20] concluded that an arbitrary s 4 (X) gives a similar solution, while the authors of Ref. [33] considered the Horndeski combination of L (4,0) and L (4,1) , i.e., with s ′ 4 = 1 4 f 4 (see the recent review [51]). …”
Section: B Black Hole Solutionsmentioning
confidence: 99%
“…[20] concluded that an arbitrary s 4 (X) gives a similar solution, while the authors of Ref. [33] considered the Horndeski combination of L (4,0) and L (4,1) , i.e., with s ′ 4 = 1 4 f 4 (see the recent review [51]). …”
Section: B Black Hole Solutionsmentioning
confidence: 99%
“…[25], Takahashi and Suyama [37], and Tretyakova and Takahashi [39]). We note that recently it has been pointed out by Babichev et al [5,6] that the conclusion of Ogawa et al [33] and Takahashi and Suyama [37] is incorrect. Now from the recent relations, various solutions for different values of C 0 and q can be obtained.…”
Section: Horndeski/galileon Spacetimementioning
confidence: 65%
“…We study static and spherically symmetric limit of black hole solutions in a subclass of general Horndeski/Galileon theories (see Maselli [29] for the case of slowly rotating black holes in Horndeski theory and also Babichev et al [4] for black hole and star solutions for Horndeski theory). The general form of the line-element for such systems with the metric signature (+, −, −, −) is described by…”
Section: Horndeski/galileon Spacetimementioning
confidence: 99%
See 2 more Smart Citations